Ocular response to environmental variations in contact lens wearers - Lopez-de la Rosa, Alberto (2017)
Purpose: To assess the influence of different indoor environments simulated in an environmental chamber on soft contact lens (CL) wearers.Methods: Fifty-four CL wearers were grouped based on their symptoms while wearing their CLs. Subjects were fitted with two different CL types, conventional hydrogel (Omafilcon A) and silicone hydrogel (comfilcon A), and exposed to two controlled indoor environmental conditions, standard [50% relative humidity (RH), 23 degrees C, 930 mb of atmospheric pressure] and adverse (in-flight air cabin environment: 5% RH, localised air flow, 23 degrees C, 750 mb atmospheric pressure), for 90 min in an environmental chamber, making a total of four visits. Symptoms, tear osmolarity, pre-lens tear breakup time (PLBUT), phenol red thread test, visual acuity, bulbar and limbal hyperaemia, corneal and limbal staining, and CL dehydration were assessed using repeated measures analysis of variance. A linear mixed model was used to analyse the effect of environment, CL type, discomfort-based grouping, and time on blink rate.Results: Environment was found to significantly (p <= 0.018) affect limbal and bulbar hyperaemia, PLBUT, tear osmolarity, and CL dehydration. Likewise, CL type significantly (p <= 0.04) affected nasal and total corneal staining, limbal conjunctival staining, CL dehydration, comfort, and blurred vision. The environment, CL type, and time had significant effects (p <= 0.0001) on the blink rate.Conclusions: Ocular surface integrity and blink rate in CL wearers depend on the environment CL users are exposed to, as well as on the soft CL type that they are wearing. Tight control of environmental conditions can contribute to a better understanding of CL-related discomfort.